2022
DOI: 10.4103/jfmpc.jfmpc_1258_21
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the Unaizah populations in Al-Qassim province in Saudi Arabia regarding nasal decongestant use for allergic rhinitis and their side effect

Abstract: Background: Nasal decongestant drugs are widely used as potent vasoconstrictive agents to reduce congestion of nasal and ocular mucous membranes in disease such as allergic rhinitis. These drugs are easily accessible to the people over the counter without prescription. The ease in access may lead the population in believing that the drugs are risk free and free from side effects. The purpose of this study was to determine the level of awareness of the people in Unaizah Al-Qassim province in Saudi A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This outcome is like the results extracted by Al-Mutairi et al, who concluded that female participants were significantly knowledgeable about the correct duration of nasal decongestant use [ 10 ]. The same study also indicated that the participants' knowledge about nasal decongestants was higher among those who had already used these medications than the others [ 10 ]. This outcome reflects that nasal decongestant users were keen to know about their medications in use.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This outcome is like the results extracted by Al-Mutairi et al, who concluded that female participants were significantly knowledgeable about the correct duration of nasal decongestant use [ 10 ]. The same study also indicated that the participants' knowledge about nasal decongestants was higher among those who had already used these medications than the others [ 10 ]. This outcome reflects that nasal decongestant users were keen to know about their medications in use.…”
Section: Discussionsupporting
confidence: 83%
“…A total of 221 (53.9%) denied the side effects of prolonged nasal decongestant use, and most participants (84.6%, n = 347) denied the contraindications for this category of medications. Similar to these findings, Al-Mutairi et al [ 10 ] found that 83.4% of their study subjects were not aware of the side effects of nasal decongestants. Therefore, health education campaigns should be provided for the public, involving information about indications, contraindications, and side effects of nasal decongestants, focusing on correct medication use, and discouraging self-medication [ 19 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This suggests that there is room for improvement in terms of public knowledge and understanding. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…A big problem of managing a patient with medication-induced rhinitis is the high risk of relapse of the disease during the next episode of use of topical nasal decongestants. Thus, according to De Corso E. et al [40], every third patient with druginduced rhinitis returns to continuous use of topical NDs one year after withdrawal. Even short-term use of topical NDs can result in the recurrence of medication-induced rhinitis in prone individuals.…”
Section: Diagnosis Of the Rhinitis Medicamentosa Is Based On The Nasa...mentioning
confidence: 99%